C-reactive protein and white blood cell count are adverse prognostic markers for patients with advanced cancer on parenteral nutrition in a palliative care unit setting: A retrospective cohort study. (March 2022) - Kieler, Markus; Kössler, Paul; Milovic, Matija; Meyer, Elias; Križanová, Kristína; Kum, Lea; Friedrich, Alexander; Masel, Eva; Bauer, Raimund; Unseld, Matthias
Background: Parenteral nutrition is controversial in patients with advanced cancer. Nevertheless, this treatment is common practice near the end of life. Aim: We aimed to identify factors which were associated with the outcome of patients on parenteral nutrition at an academic tertiary palliative care unit. Design: In this retrospective cohort study patients were assigned to two groups according to parenteral nutrition treatment. Inferential statistics were used to assess whether the dynamics of laboratory variables over 2 weeks of parenteral nutrition were associated with survival. Setting/Participants: Patients admitted to the Department of Palliative Medicine at the Medical University of Vienna between 2016 and 2018 were included in this study. Results: Of 443 patients, 113 patients received parenteral nutrition. Patients had a lower body mass index, lower levels of bilirubin, γ-glutamyltransferase, alkaline phosphatase, and were of younger age compared to patients which did not receive parenteral nutrition. No difference in survival as measured from admission to death was found when comparing the two groups. Levels for γ-glutamyltransferase, alkaline phosphatase, and C-reactive protein significantly increased during 2 weeks of parenteral nutrition. Among patients with parenteral nutrition, an increase in C-reactive protein or white blood cell count levels was associated with lower survival. Conclusion: Patients who responded with an increase of C-reactive protein or white blood cell count during 2 weeks after reinitiation or start of parenteral nutrition had a worse survival. Our findings might support clinicians and patients in their decision to forgo parenteral nutrition in a palliative care setting.